Synthesis and pharmacological evaluation of multifunctional tacrine derivatives against several disease pathways of AD. Issue 4 (15th February 2015) - Digiacomo, Maria; Chen, Ziwei; Wang, Shengnan; Lapucci, Annalina; Macchia, Marco; Yang, Xiaohong; Chu, Jiaqi; Han, Yifan; Pi, Rongbiao; Rapposelli, Simona
Graphical abstract